2011
DOI: 10.1128/aem.05358-11
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction of Acetaldehyde and Hydrogen during Glucose Fermentation by Escherichia coli

Abstract: Escherichia coli K-12 strain MG1655 was engineered to coproduce acetaldehyde and hydrogen during glucose fermentation by the use of exogenous acetyl-coenzyme A (acetyl-CoA) reductase (for the conversion of acetylCoA to acetaldehyde) and the native formate hydrogen lyase. A putative acetaldehyde dehydrogenase/acetylCoA reductase from Salmonella enterica (SeEutE) was cloned, produced at high levels, and purified by nickel affinity chromatography. In vitro assays showed that this enzyme had both acetaldehyde dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
1
32
1
Order By: Relevance
“…The Arabidopsis AtLpxD1 (primers H13 and H14) and AtLpxD2 (primers H15 and H16) genes (the 59 CDS that encodes the putative mitochondrial presequences was removed) were cloned into pBE522 vector (Zhu et al, 2011), resulting in AtlpxD1-pBE and AtlpxD2-pBE. In the presence of AtlpxD1-pBE or AtlpxD2-pBE, the lpxD gene of the E. coli BL21* strain was replaced by a Gen R cassette using a PCR-based method (Datsenko and Wanner, 2000) with primers H17 and H18.…”
Section: E Coli Strains and Lipid A Analysesmentioning
confidence: 99%
“…The Arabidopsis AtLpxD1 (primers H13 and H14) and AtLpxD2 (primers H15 and H16) genes (the 59 CDS that encodes the putative mitochondrial presequences was removed) were cloned into pBE522 vector (Zhu et al, 2011), resulting in AtlpxD1-pBE and AtlpxD2-pBE. In the presence of AtlpxD1-pBE or AtlpxD2-pBE, the lpxD gene of the E. coli BL21* strain was replaced by a Gen R cassette using a PCR-based method (Datsenko and Wanner, 2000) with primers H17 and H18.…”
Section: E Coli Strains and Lipid A Analysesmentioning
confidence: 99%
“…Producing these compounds using microbes would be a renewable alternative to current methods. However, microbial hosts such as E. coli are plagued by many highly active endogenous aldehyde reductases (ALR) that convert aldehydes to alcohols (Rodriguez and Atsumi, 2012; Zhu et al, 2011), which greatly complicates strain engineering for aldehyde production. As a result, E. coli production of only acetaldehyde (Zhu et al, 2011) and isobutyraldehyde (Rodriguez and Atsumi, 2012) has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…The first reaction converts ethanolamine to acetaldehyde and ammonia and is catalyzed by the B 12 -dependent ethanolamine-ammonia lyase EutBC (7). In the second reaction, the EutE enzyme catalyzes oxidation of acetaldehyde to acetyl-CoA, thereby consuming CoA and reducing NAD ϩ to NADH (7,8). At this point, acetyl-CoA could be shunted directly into the tricarboxylic acid (TCA) cycle to serve as a carbon and energy source (see the horizontal reaction sequence in Fig.…”
mentioning
confidence: 99%